Domination on cactus chains of pentagons - Mihajlov Carević, Miroslava (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: A graph as a mathematical object occupies a special place in science. Graph theory is increasingly used in many spheres of business and scientific fields. This paper analyzes pentagonal cactus chains, a special type of graphs composed of pentagonal cycles in which two adjacent cycles have only one node in common. The aim of the research is to determine the dominant set and the dominance number on ortho and meta pentagonal cactus chains.Methods: When the corresponding destinations are treated as graph nodes and the connections between them as branches in the graph, the complete structure of the graph is obtained, to which the laws of graph theory are applied. The vertices of the pentagon are treated as nodes of the graph and the sides as branches in the graph. By applying mathematical methods, the dominance was determined on one pentagon, then on two pentagons with a common node, and then on ortho and meta pentagonal cactus chains.Results: The research has shown that the dominance number on the ortho chain Oh of the length h ≥ 2 is equal to the value of the expression [3h/2]  while on the meta chain Mh it is equal to the value of the expression h+1, which was proven in this paper.Conclusion: The results show that the dominant sets and the dominance numbers on ortho and meta pentagonal cactus chains are determined and explicitly expressed by mathematical expressions. They also point to the possibility of their application in the fields of science as well as in the spheres of business in which these structures appear.
Keywords: graph; pentagonal cactus-chain; dominant set; dominance number